(untitled) (Eurasian Journal of History, Geography and Economics, 2025)
This study investigates the integration of geographical and GIS-based methods for analyzing hydrogeological processes in the Balıkesir region of Türkiye. The research combines digital elevation modeling, remote sensing, and spatial hydrogeological data to identify groundwater recharge zones, aquifer systems, and the influence of topography on subsurface water movement. GIS tools such as ArcGIS and QGIS were used to process topographic, geological, and satellite datasets, while interpolation and overlay analyses were performed to visualize groundwater depth and flow dynamics. The results show that topography, lithology, and land cover significantly influence groundwater distribution. The study demonstrates that GIS provides an effective framework for integrating multi-source data to support sustainable groundwater management and environmental planning.